Perception of selected strategic management factors of SME in V4 countries - Belás, Jaroslav; Damborský, Milan; Metzker, Zdenko; Šuleř, Petr (Serbian Journal of Management, 2021)
The objective of the paper was to present current theoretical findings in the area of strategic management of small and medium-sized enterprises (SMEs) in the Visegrad Four (V4) countries. Within the stated objective, the weight of individual strategic management factors was quantified and trends in the Czech Republic were compared with other V4 countries. Empirical research was conducted between October 2019 and March 2020 in V4 countries by means of an online questionnaire. The overall number of accepted questionnaires was as follows: Czech Republic (CR): 454, Slovak Republic (SR): 368, Poland (PL): 364, and Hungary (HU): 399. Questionnaires were completed by company owners and top managers. The empirical research provided several interesting findings. On the one hand, SMEs confirmed that strategic management is an important part of corporate management; on the other hand, strategic management is not implemented in the everyday life of SMEs and is not implemented through action plans and programmes. The level of agreement with the statement that quality strategic management improves the competitiveness of enterprises and their stability in domestic and foreign markets was not very high. Not surprisingly, SMEs have significant weaknesses in monitoring and personal risk management. The research results point to the need for increasing the level of strategic risk management in the segment of SMEs, which is an important factor in improving their competitiveness in a globalizing economic environment.